2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-Glucoside improves female ovarian aging - Lin, Hung-Yun; Yang, Yung-Ning; Chen, Yi-Fong; Huang, Tung-Yung; Crawford, Dana R.; Chuang, Hui-Yu; Chin, Yu-Tang; Chu, Hung-Ru; Li, Zi-Lin; Shih, Ya-Jung; Chen, Yi-Ru; Yang, Yu-Chen S. H.; et al. (Frontiers in Cell and Developmental Biology, 2022)
Reduced fertility associated with normal aging may reflect the over-maturity of oocytes. It is increasingly important to reduce aging-induced infertility since recent trends show people marrying at later ages. 2,3,5,4′-Tetrahydroxystilbene-2-O-β-D-glucoside (THSG), a polyphenol extracted from Polygonum multiflorum, has been reported to have anti-inflammatory and anti-aging properties. To evaluate whether THSG can reduce aging-related ovarian damage in a female mouse model of aging, THSG was administered by gavage at a dose of 10 mg/kg twice weekly, starting at 4 weeks of age in a group of young mice. In addition, the effect of THSG in a group of aged mice was also studied in mice starting at 24 weeks of age. The number of oocytes in the TSHG-fed group was higher than in the untreated control group. Although the percentage of secondary polar bodies (PB2) decreased during aging in the THSG-fed group, it decreased much more slowly than in the age-matched control group. THSG administration increased the quality of ovaries in young mice becoming aged. Western blotting analyses also indicated that CYP19, PR-B, and ER-β expressions were significantly increased in 36-week-old mice. THSG also increased oocyte numbers in aged mice compared to mice without THSG fed. Studies of qPCR and immunohistochemistry (IHC) analyses of ovaries in the aged mice groups were conducted. THSG increased gene expression of anti-Müllerian hormone (AMH), a biomarker of oocyte number, and protein accumulation in 40-week-old mice. THSG increased the expression of pgc1α and atp6, mitochondrial biogenesis-related genes, and their protein expression. THSG also attenuated the fading rate of CYP11a and CYP19 associated with sex hormone synthesis. And THSG maintains a high level of ER-β expression, thereby enhancing the sensitivity of estrogen. Our findings indicated that THSG increased or extended gene expression involved in ovarian maintenance and rejuvenation in young and aged mice. On the other hand, THSG treatments significantly maintained oocyte quantity and quality in both groups of young and aged mice compared to each age-matched control group. In conclusion, THSG can delay aging-related menopause, and the antioxidant properties of THSG may make it suitable for preventing aging-induced infertility.